Cognitive Insight in Schizophrenia: Its Relationship with Verbal Learning and Clinical Insight - Othman, Zahiruddin; Chong, Teck Lua (Japan International Cultural Exchange Foundation, 2018)
Background: Cognitive insight is a relatively new concept. While cognition, clinical and cognitive insight are interrelated, the relationship is rather complex and the research so far is inconclusive. Objectives: This study aimed to examine cognitive insight and its relationships with verbal learning, clinical insight, and severity of psychopathology among schizophrenia outpatient in Kelantan, Malaysia. Methods: A total of 108 stable outpatient schizophrenia patients were recruited. Cognitive insight, psychopathology, verbal learning, and clinical insight were assessed using the Beck Cognitive Insight Scale (BCIS), Brief Psychiatric Rating Scale (BPRS), Auditory Verbal Learning Test (AVLT), and Insight and Treatment Attitudes Questionnaire (ITAQ), respectively. Results: In multiple linear regression final model for BCIS-Composite, only female gender emerged as a significant associated factor. The final equation for BCIS-Composite was 2.746 + 1.99*(Gender) with 4% of the variation explained by gender (R2 = 0.04). None of the other socio-demographic and clinical characteristics including psychopathology, clinical insight and verbal learning were significantly associated with the self-reflection, self-certainty and composite-index of cognitive insight Conclusions: Cognitive insight was not significantly associated with verbal learning, clinical insight, and severity of psychopathology. The only significant factor was female gender which was positively correlated with composite-index of cognitive insight.